PENUGASAN TENAGA KERJA BAGIAN PRODUKSI PADA PT. SAMARINDA CENDANA COLD STORAGE DAN INDUSTRI DI ANGGANA - Heriyanto Heriyanto (Prodi Ilmu Administrasi Negara, 2015)
The study was conducted at PT. Samarinda Sandalwood Cold Storage dan Industry in Anggana during the month of February-March 2014, the data obtained from this study that there has been a decay of black shrimp ranged 20-30kg produced. This decay occurs because the black shrimp raw material processing completed different times that the processing starts at 07.30 am and finishes approximately at 9:30 to 10:00 am. Analysis using the Hungarian method of calculation results show after organized labor assignments on the production of sub-section 5 in particular processing variations working group (Task: Cleaning, Proofreading, washing, weighing and preparation) obtained with the Hungarian method of processing completion time of 110 minutes more lower than the standard completion time of the company to task 5 variations of the working group that is equal to 150 minute. Thus assignments to 5 working group of optimal variation can be achieved by the company as follows:1. Cleaning job is assigned to the working group III obtained sebsar 45 minute turnaround time for the production activities. 2. The work assigned to the correction of the working group II obtained completion time by 15 minutes for the production activities. 3. Washing job is assigned to the working group IV obtained completion time is 30 minutes for the production activities. 4. Weighing job assigned to working groups I obtained completion time is 30 minutes for the production activities. 5. Job assigned to the working group drafting the V obtained completion time is 30 minutes for the production activities. Processing is done for 150 minutes (finished at 10:00) resulted in the decay of black shrimp occur as much as 30 kg mean damage costs of raw materials amounting to Rp. 4.35 million, - if the processing is done for 150 minutes (finished at 09.30) decay can be pressed into a 20 kg + constant, meaning the cost of raw material damage amounting to Rp. 2.900.000.- it can save the cost of raw material damage amounting to Rp. 1.450.000, -